American economic relations with the Federal Republic of Germany and with Japan - Martin Bronfenbrenner (Intereconomics, 1978)
Disagreement on appropriate policies to reduce the American balance of payments deficit has been a major source of friction between the US, on the one hand, and the Federal Republic of Germany and Japan, on the other. Against this background Professor Bronfenbrenner Presents a theoretical analysis of how deficit countries may proceed to solve their problems, passing on to point out, in terms of this general analysis, what the US is doing and what Germany and Japan would like it to do.
Keywords: 330; Balance Of Payments